Temporal evolution of anchor tracks on a silty seafloor (Eckernförde Bay/Baltic Sea) - Schulze, Inken; Schönke, Mischa; Feldens, Peter; Papenmeier, Svenja (Frontiers in Remote Sensing, 2025)
Anchoring activities exert significant physical pressure on seabed, altering benthic habitats through mechanical disturbances. The European Marine Strategy Framework Directive mandates the assessment of such anthropogenic impacts. Evaluating seabed integrity requires an understanding of both the spatial extent of disturbance and the rate of recovery. This study presents multibeam echosounder bathymetry and backscatter from a heavily impacted area in the Bay of Eckernförde, German Baltic Sea, a region with intensive tourist and naval shipping traffic. The data reveal a dense network of anchor tracks, characterized by elongated furrows flanked by mounds to both sides and extensive abrasion zones caused by the anchor chains. The profile of a fresh anchor track shows a depth of −0.3 m and a mound elevation of 0.2 m, both features diminishing by approximately half after 1 year. Its initial anchor impact crater reaches maximum depth of 0.7 m in the silty sediments. Seafloor disturbance extends approximately 3 m to both sides from anchor tracks, affecting approximately 20% of the surveyed area, excluding widespread abrasion zones. To analyze track degradation, a relative timeline was constructed using a topological sorting algorithm and compared with absolute dating based on AIS data. Results indicate slope measurements effectively capture anchor track degradation until morphological equilibrium is reached. Beyond this stage, tracks remain visible in backscatter data by increased intensity along former mounds. This suggests that anchor tracks have a more persistent impact on seabed integrity than bathymetric data indicate. The spatial extent and the long-lasting effect of the anchor tracks highlight the necessity for explicit spatial management strategies to mitigate cumulative impacts on seabed integrity.